What Predicts Individuals’ Disidentification? The Joint Effect of Fearful Attachment and Social and Economic Exchanges (Journal of Organizational Psychology, 2017)
Integrating attachment and exchange theories, we examined the joint effect of fearful attachment and two types of exchange behavior (social and economic exchange) on individuals’ disidentification from the organizations. Results indicated that fearfully attached individuals reported more disidentification when they engaged in both low social exchanges and high economic exchanges with their organizations. From a practical standpoint, reducing individuals’ disidentification can be accomplished by organizations, leaders, or coworkers who need to emphasize their social exchanges and deemphasize their economic exchanges with the focal individual.
Keywords: Organizational Psychology; Economic Exchanges